Korelasi antara Pengalaman Praktik Kerja Industri, Hasil Belajar dan Kemandirian Belajar dengan Kesiapan Kerja Peserta Didik Sekolah Menengah Kejuruan - Hikmah, Saniyatul; Rijanto, Tri; Joko, Joko (Jurnal Pendidikan Teknik Elektro, 2024)
This study aims to identify the correlation between industrial work practice experience, learning outcomes of electric motor installation, and learning independence with the work readiness of TITL grade XII students, both individually and together. The type of research used is ex post facto with the population of students of the Electrical Power Installation Engineering (TITL) expertise program at SMKN 7 Surabaya and SMKN 2 Lamongan. The data collection technique involves the use of questionnaires for the variables of industrial work practice experience (X1), learning independence (X3), and job readiness (Y). Meanwhile, documentation was used to collect data on the learning outcome variable of electric motor installation (X2). The data analysis in this study includes prerequisite tests such as normality test, linearity test, multicollinearity test, and homoscedasticity test. Hypothesis testing is carried out using correlation and multiple regression techniques with the help of SPSS version 25 software for Windows. The results of this study are (1) There is a significant correlation between the experience of industrial work practices and the work readiness of class XII TITL students, (2) There is a significant correlation between the learning outcomes of Electric Motor Installation and the work readiness of class XII TITL students, (3) There is a significant correlation between learning independence and work readiness of class XII TITL students, and (4) There is a significant correlation between industrial work practice experience, learning outcomes of Electric Motor Installation, learning independence with the work readiness of class XII TITL students.